Clinical outcome of endoscopic retrograde cholangiopancreatography for choledocholithiasis in end-stage renal disease patients on hemodialysis - Park, Jin-Seok; Jeong, Seok; Cho, Jae Hee; Kwon, Chang-Il; Jang, Sung Ill; Lee, Tae Hoon; Han, Joung-Ho; Hwang, Jae Chul; Lee, Don Haeng (Turkish Journal of Gastroenterology, 2020)
Background and Aim: Endoscopic retrograde cholangiopancreatography (ERCP) is used as a curative method for choledocholithiasis, but little is known about ERCP for patients with end-stage renal failure (ESRD) on hemodialysis (HD). The aim of the current study was to evaluate the efficacy and safety of ERCP for patients with ESRD on HD and to identify the risk factors of ERCP-related bleeding.Methods: The medical records of 61 ESRD patients with choledocholithiasis that underwent ERCP were retrospectively investigated with respect to successful bile duct stone removal and procedure-related adverse events, such as, pancreatitis, bleeding, and cholangitis.Results: For all study subjects, the stone removal success rate was 96.7 % and the overall ERCP-related adverse event rate was 21.3 % (pancreatitis, 4.9%; bleeding, 13.1%; cholangitis, 6.6%). Endoscopic sphincterotomy (EST) was found to be associated with hemorrhage (P=0.02), and the occurrence of hemorrhage in patients that underwent EST with or without EPBD was significantly higher than that in patients who underwent endoscopic papillary balloon dilation alone (Odds ratio 1.27, 95% confidence interval 1.075-1.493, P=0.02). Conclusion: ERCP for ESRD patients was found to be feasible and safe. However, the receipt of EST was significantly related to hemorrhagic events. Endoscopic papillary balloon dilatation reduced the risk of hemorrhage and was as effective as EST in terms of stone removal.